Trend Analysis of Financial Statements in the Plantation Sub-Sector Listed on the Indonesia Stock Exchange 2016 – 2020 period - Iftita Haz Qurnia; Febrianty Febrianty (Jurnal Ekonomi LLDIKTI Wilayah 1 (JUKET), 2022)
This study aims to determine or understand the analysis of financial statements in the plantation sub-sector listed on the Indonesian stock exchange using trend analysis. The research method used is a quantitative method with a descriptive approach. The data collection technique used in this research is through the documentation of the financial statements of the plantation sub-sector companies. The results of the study based on trend analysis of the five companies on the balance sheet show good conditions because the percentage has increased every year. On the income statement, there are still companies that show poor results because the percentage every year there are still deficits and losses. In the five cash flow statements, many companies experienced a deficit and the percentage decreased so that the company showed poor results.